Pengembangan Nasionalisme Generasi Muda di Era Globalisasi - Widiyono, S (Universitas Widya Mataram, 2019)
The sense of nationalism is very important for the young generation of Indonesia to be able to become a developed nation, a modern nation, a nation that is safe, and peaceful, just and prosperous in the midst of globalization that increasingly challenges the Indonesian state. As a nation and country in the midst of other nations in the world, it requires a high nationalism identity of citizens, especially among the young generation of Indonesia. The spirit of nationalism is still needed by the existence of the Indonesian nation and state. High nationalism from citizens or the younger generation will make positive and best behavior for the nation and state. In the current era of globalization there are several trends of depletion of the spirit of nationalism among the younger generation. This can be seen from a number of benchmarks, namely the lack of appreciation of the younger generation of Indonesian native culture, patterns and lifestyles of Westernized teenagers, and so on. To overcome this problem, it is necessary to have an intensive and continuous movement in the world of education related to the planting of a sense of nationalism towards students from elementary to tertiary levels that must be done by teachers and lecturers by respecting and being proud of indigenous Indonesian culture. In this paper the author tries to explain the circumstances and facts about the development of nationalism through library studies.